MOISSANITE FROM PERVOMAISKY VOLKANIC PIPE VOLCANOGENIC ROCKS IN NORTERIN KRIVOROZHIE - VELIKANOV, YU.; VELIKANOVA, O.; NOZHENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The finding of moissanite accompanied by other minerals – diamond complementary rocks, is a primary prospecting feature, by analogy with Eastern-Siberian platform kimberlites, sustaining availability of kimberlite type volcanic pipes in Northern Krivorozhie.